Length-weight relationship, condition factor and gonado-somatic index of Labeo calbasu (Hamilton, 1822) - Vahneichong, E; Das, Sudhir Kumar; Mondal, Anandamoy; Bhakta, Dibakar (Journal of Fisheries, 2018)
An attempt was made to study dynamics of length-weight relationship (LWR), relative condition factor (Kn) and gonado-somatic index (GSI) of Labeo calbasu from the wetlands of South 24 Parganas district of West Bengal, India. A total of 275 fish specimens (130 to 430 mm) were examined over nine months from December 2006 to August 2007. Specimens were categorized into two groups based on the size at first maturity of 260 mm. The LWR was recorded W = 0.007269 L3.181 for Group A (<260 mm) and W = 0.007367 L3.031 for Group B (≥260 mm). The individuals exhibited isometric growth. The monthly mean Kn values varied from 0.924 to 1.141 with an average value of 1.059. The mean monthly values of GSI varied from 0.544 to 3.301 for male and 0.560 to 9.649 for female. There was significant variation (P < 0.05) in the mean values of GSI in different months between sexes.